The pride of place : local memories & political culture in nineteenth-century France - Gerson, Stéphane (Cornell University Press, 2003)
Nineteenth-century France grew fascinated with the local past and thousands of citizens embraced local archaeology, staged historical pageants and created museums. The author provides a cultural and political history of this 'cult of local memories'.
Keywords: France -- Cultural policy.; Regionalism -- France -- History -- 19th century.; Politics and culture -- France -- History -- 19th century.; Decentralization in government -- France -- 19th century.; National characteristics, French.; Elite (Social sciences) -- France.; Régionalisme -- France -- Histoire -- 19e siècle.; Politique et culture -- France -- Histoire -- 19e siècle.; Français.; Élite (Sciences sociales) -- France.; 15.70 history of Europe.; Cultural policy; Decentralization in government; Elite (Social sciences); National characteristics, French; Politics and culture; Regionalism; France; Dezentralisation; Elite; Geschichtsbewusstsein; Kulturpolitik; Politische Kultur; Provinz; Regionalismus; Frankreich; Kollektives Gedächtnis; Nationale identiteit.; Decentralisatie.; SOCIAL SCIENCE -- Sociology -- General.; Geschichte 1800-1900.; 1800-1899; History